Customer Relationship Management - wdrażanie w przedsiębiorstwie na przykładzie Telekomunikacji Polskiej SA - Łopaciński, Karol (Customer relationship management - putting into practice in the company using the Telekomunikacja Polska SA example, 2005)
The first part of the article presents the essence of CRM and stages of putting it into practice in the firm, with the special emphasis on the operating and analytic CRM. The second part was devoted to the Customer Relationship Management in economic practice. Telekomunikacja Polska SA example has been used. The process of introducing CRM was presented and the importance of the Call Center and Back Office in this process. The opinions about CRM in TP SA have proved a number of mistakes: insufficient defining of business processes, weak guidelines of CRM communication in the company, staff unprepared and wrong adjustments of the information system.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (8); 2005; nr 1094, s. 61-73